Workplace happiness matters / Rosliza Md Zani and Shuhaimi Samanol - Md Zani, Rosliza; Samanol, Shuhaimi (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Happiness is the first thing that we want to achieve in life, as well as at work, and is of great importance to most people. Happiness has become a goal that is highly valued in most societies. Feeling happy is the foundation of the human experience, and most people want to be happy wherever they are. Going to the office, mechanically doing all the assigned tasks, and coming home to spend the rest of the day with a drink in hand and a TV in front is an ideal picture of unhappy life (Chowdury, 2020). On the other side, happy employees will arrive at the office on time because they respect punctuality and will do all the daily tasks as they enjoy doing them. They will work lovingly and passionately, not out of coercion.